Ferritin exhibits Michaelis–Menten behavior with oxygen but not with iron during iron oxidation and core mineralization. Issue 4 (5th February 2019) - Bou-Abdallah, Fadi; Flint, Nicholas; Wilkinson, Tyler; Salim, Samantha; Srivastava, Ayush Kumar; Poli, Maura; Arosio, Paolo; Melman, Artem
Abstract : Iron uptake into mammalian ferritins reveals oxygen (but not iron) saturation kinetics and physiologically relevant K m, O2 values. Abstract : The excessively high and inconsistent literature values for K m, Fe and K m, O2 prompted us to examine the iron oxidation kinetics in ferritin, the major iron storage protein in mammals, and to determine whether a traditional Michaelis–Menten enzymatic behavior is obeyed. The kinetics of Fe(ii ) oxidation and mineralization catalyzed by three different types of ferritins (recombinant human homopolymer 24H, HuHF, human heteropolymer ∼21H:3L, HL, and horse spleen heteropolymer ∼3.3H:20.7L, HosF) were therefore studied under physiologically relevant O2 concentrations, but also in the presence of excess Fe(ii ) and O2 concentrations. The observed iron oxidation kinetics exhibited two distinct phases (phase I and phase II), neither of which obeyed Michaelis–Menten kinetics. While phase I was very rapid and corresponded to the oxidation of approximately 2 Fe(ii ) ions per H-subunit, phase II was much slower and varied linearly with the concentration of iron(ii ) cations in solution, independent of the size of the iron core. Under low oxygen concentration close to physiological, the iron uptake kinetics revealed a Michaelis–Menten behavior with K m, O2 values in the low μM range ( i.e. ∼1–2 μM range). Our experimental K m, O2 values are significantly lower than typical cellular oxygen concentration, indicating that iron oxidation and mineralization in ferritin should not be affected by the oxygenation level of cells, and should proceed even under hypoxic events. A kinetic model is proposed in which the inhibition of the protein's activity is caused by bound iron(iii ) cations at the ferroxidase center, with the rate limiting step corresponding to an exchange or a displacement reaction between incoming Fe(ii ) cations and bound Fe(iii ) cations.